(3jJjeI GdOgQ aj eMGSf Cgd GdYUQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NjQ eG HOi Hg GdcdGe hNJe s
(3BNQgG (B:s
(3jfJgi CKfGA JQLeI CHhdMSf Ydi Hf YHOGdQMef Hf jhfS GdefLe s
(3GdehLhO efgG GdLRA Gdhds
(3GfXQ Qbe(B" 897-901,1310,2175" (3COHs
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B284 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B339 s
Keywords: (3GdJGQjNs